Oleksandr Potebnya and Linguistics of Emotions - Сліпецька, Віра Дмитрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The article focuses on the attempt to generalize the system of O. Potebnya’s views on the problem of linguistics of emotions; to prove that in a modern linguistics of emotions O. Potebnya’s postulates are taken into account and developed concerning the peculiarity of verbalization of feelings, emotions and will in a text (discourse); concerning the status of interjection as a grammatic marker of emotions; functioning of an emotional language picture.